Climatic Controls on the Interannual Variability of Shelf Circulation in the Northern South China Sea. Issue 7 (28th June 2022) - Deng, Yongfei; Liu, Zhiqiang; Zu, Tingting; Hu, Jianyu; Gan, Jianping; Lin, Yuxin; Li, Zhibing; Quan, Qi; Cai, Zhongya
Abstract: We comprehensively investigate the interannual variability of multi‐scale motions in the northern South China Sea (NSCS) and associated influences from the terrestrial, atmospheric, and oceanic processes over the period 1994–2018 based on observations and a numerical simulation. We find that the interannual variabilities of the NSCS circulation and hydrographic properties, in the form of a cross‐scale interactive dynamic system, are sensitive to the tropical climate variability represented by the El Niño–Southern Oscillation (ENSO). In coastal areas with less than 30 m depth, the anomalous warm (cold) and less (more) saline waters are regulated by the rate of Pearl River discharge due to the predominant precipitation (evaporation) and positive (negative) heat‐flux anomaly in the Pearl River catchment in El Niño (La Niña) years. Controlled by the interannual variabilities of slope current and atmospheric forcings, the shelf current at 30–200 m depth responds asymmetrically to the ENSO, which establishes a stronger northeastward flow anomaly in El Niño years than the southwestward flow anomaly in La Niña years. We further show that the interannual variability of the slope current is jointly governed by the atmospheric and oceanic processes that tend to offset each other in interannual timescales. In particular, the weakened (strengthened) cyclonic wind stress curl over the ocean basin tends to moderate (intensify) the slope current in the NSCS, while this process is mitigated by the stronger (weaker) Kuroshio intrusion in El Niño (La Niña) years. Plain Language Summary: The oceanic circulations and biogeochemical processes of shelf seas of the world's oceans have long been recognized to be concurrently impacted by the terrestrial, oceanic, and atmospheric forcings. However, the climatic controls and respective function of those forcings in regulating the interannual variability of shelf circulations in the northern South China Sea (NSCS) have not been thoroughly investigated. This research comprehensively studies the interannual variabilities and joint functions of those forcings in the NSCS. This research relies on valuable long‐term observations and well‐validated numerical simulation, and demonstrates that hydrographic properties in the coastal seas to the west of the Pearl River Estuary (PRE) are sensitive to the interannual variability of terrestrial forcings sourced from the Pearl River catchment. A large volume of warm and fresh waters is established when the extensive air‐sea‐land interactions in and around the southern China notably elevate the riverine discharges in El Niño years. Shelf circulations are mainly influenced by interannual changes of the prevailing winds, which drive northeastward shelf current anomalies in El Niño years. The slope current illustrates a southwestward anomaly, elevates the shoreward cross‐shelf pressure gradient force and strengthens the northeastward anomaly of shelf current in El Niño years. Key Points: Shelf current in the northern South China Sea shows extensive interannual variability Terrestrial forcings determines interannual variability of hydrographic properties of coastal oceans to the west of Pearl River Estuary The shelf current shows notable asymmetric responses to interannual changes of winds over the shelf